Ainda encantados? neoateísmo e desencantamento do mundo - Moreira, Leonardo Vasconcelos de Castro (2014)
Richard Dawkins, Daniel Dennett, Sam Harris and Christopher Hitchens have started the new atheism movement. After the terrorist attacks on September 11, 2001, these authors aligned their speeches, which were already anti-religious, even more vehemently. Using the concept of Max Weber's disenchantment of the world, I tried to understand how they use science and other arguments against religion. Without forgetting the political struggle, I observe how the deconstruction of the religious sense has a goal of conversion. With theempty of the religious morality of theirs followers, I examine how these four authors construct a new worldview, at an individual and collective level, that would be the (re)enchantment of the world proposed by them. The replacement of religious values by the values of science and new-atheist values, places the new atheism not only on a collision course towards religions, but also causes this new movement to cross to the side of the religious field and become a new symbolic proposal with their own values